Book Review: The Little Book of Behavioral Investing - Nadia Bahadori (Journal of Financial Therapy, 2016)
The Little Book of Behavioral Investing: How Not to Be Your Own Worst Enemy, written by James Montier provides his readers with 16 chapters of prevalent behavioral challenges and mental mistakes that are commonly experienced by everyday investors.
Keywords: book review; investing; financial therapy